Development of individualized medicine for epilepsy based on genetic information. Issue 5 (September 2008) - Kaneko, Sunao; Yoshida, Shuichi; Kanai, Kazuaki; Yasui-Furukori, Norio; Iwasa, Hiroto
Despite the continuous development and release of new anti-epileptic drugs (AEDs), almost one in four patients are resistant to AED therapy. Current therapy requires trial and error to determine the most effective AED and dosage for a patient. The development of individualized medicine for epilepsy is critical for improving AED treatment, particularly that based on genetic information. However, several crucial issues remain to be resolved before the development of AED therapy can proceed further. The epilepsy genes responsible for common phenotypes have not yet been identified and ongoing pharmacogenetic studies continue to search for an explanation as to why 20–25% of patients do not respond to AEDs. There is no convincing clinical evidence that P-glycoprotein at the blood–brain barrier limits the uptake of AEDs into the brain of epileptic patients and contributes to the development of the drug-resistant phenotype. This article provides a critical review of the status and perspectives for the development of individualized medicine for epilepsy, based on genetic polymorphisms/mutations in relation to three major components: the pharmacodynamic pathway, the pharmacokinetic pathway and the mechanisms of action of AEDs. The development of multiplex assay technologies, together with the generation of epilepsy animal models bearing human epilepsy genes, are also discussed.